1988
DOI: 10.1177/0022427888025003003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race in Juvenile Justice Processing

Abstract: This article examines the effect of defendant's race on juvenile justice processing in a large southern state. The study traces the movement of a cohort of over 50,000 youths through multiple decision-making stages from intake screening to judicial disposition. After controlling for legal and processing variables in multivariate analyses, we find that race has a direct effect on decisions made at several processing junctures. Indirect and cumulative effects of race are also addressed and implications for futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
156
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(167 citation statements)
references
References 42 publications
10
156
0
Order By: Relevance
“…Further, the racial disparities occur in multiple decision points. For example, Bishop and Frazier (1988) found that Blacks were more likely to be formally processed, referred to court, adjudicated delinquent, and received more severe dispositions than White juveniles. Similarly, Pope and Feyerherm (1990) found that…”
Section: Purpose Goals and Objectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…Further, the racial disparities occur in multiple decision points. For example, Bishop and Frazier (1988) found that Blacks were more likely to be formally processed, referred to court, adjudicated delinquent, and received more severe dispositions than White juveniles. Similarly, Pope and Feyerherm (1990) found that…”
Section: Purpose Goals and Objectivesmentioning
confidence: 99%
“…Studies have also shown that legal factors such as offense seriousness, prior record, and probation violations are stronger predictors of detention status and prosecutorial referral than race (Bishop & Frazier, 1996;Bishop & Frazier, 1988;O'Neil, 2002;Hindelang, 1978;Gottfredson & Hirschi, 1990;Lynch, 2002).…”
Section: Purpose Goals and Objectivesmentioning
confidence: 99%
See 3 more Smart Citations